The role of learning interaction in Open & Distance Learning (ODL): Issues, experiences and practices - Dzakiria, Hisham (UUM Press, 2008)
This book of readings is about one specific but vital aspect of Open Distance Learning (ODL): The Role of ‘Learning Interaction’ in Open & Distance Learning: Issues, Experiences and Practices.In many ways, interaction and interactivity have not received the attention warranted. The learning conditions are quite different for distance learners as compared with the conventional type of learning where face to face (f2f) meeting between students and instructors are common.This may affect learning outcomes significantly in ODL.There needs to be a strong emphasis on the provision of learning interactions as a means of support, which is designed to facilitate learning between the learners and the teachers with the course content. Interaction is a very important component of ODL.Evidently, it has been proven by various research that learning without sufficient interaction possibly could lead the learners to delay their completion of a programme or drop out altogether.In short, ODL without sufficient learning interactions within the primary stakeholders (namely the students and the teachers), will not succeed.The target audience of this book is a wide range of staff either currently on ODL schemes, or about to start.They may be distance teachers, tutors, ODL policy makers, advisers, counselors working directly with distance learners or administrators and managers organising learning support in ODL.